On the effect of surface recombination in thin film solar cells, light emitting diodes and photodetectors - Ardalan Armin (Synthetic Metals, 2019)
Radiative and non-radiative charge carrier recombination in thin-film diodes plays a key role in determining the efficiency of electronic devices made of next generation semiconductors such as organic, perovskite and nanocrystals. In this work, we show that lowering the bulk recombination does not necessarily result in enhanced performance metrics of electronic devices. From the perspective of charge carrier extraction and injection, the radiative limit of the open-circuit voltage of solar cells, noise current of photodetectors and lasing threshold of injection lasers cannot be improved if the contacts are not perfectly selective. A numerical drift-diffusion model is used to investigate the interplay between bulk recombination and surface recombination of minority carriers at the contacts in bipolar thin diode devices based on low-mobility semiconductors. The surface recombination becomes prominent in case of reduced bulk recombination strengths when non-selective contacts, i.e., contacts that are either metallic or have imperfect charge-selective interlayers, are employed. Finally, we derive analytical approximations for the case when diffusion-limited surface recombination of minority carriers at Ohmic contacts dominates the dark current. These results indicate that having perfectly selective contacts becomes crucial in systems with suppressed bulk recombination – a challenging requirement for the future state-of-the-art thin-film solar cells, light-emitting devices and photodetectors made of next generation semiconductors.